The Measurement of different mechanical components using Machine Vision and digital image processing - Ram Prakash T; M.Rishidev; N. Vignesh; S.A Vishnu Bahavath (Journal of Advanced Mechanical Sciences, 2024)
Machine vision system is a technology that employs a computing device to inspect, evaluate, and identify still or moving parts.  Post the acquisition of the image, it is processed, analysed and measured by various computer software in determining various characteristics.  The role of machine vision in accurately measuring the dimensions of complex parts is inevitable.  In this study an attempt has been made to accurately measure the dimensions of the boat shaped structure of the single way tool post which is used in machining process and in measuring the indentation diameter of the specimen used in Brinell Hardness.  DMV 001 camera was used, and various lighting intensities and techniques have been employed during the image acquisition.  A plethora of sensors and a myriad of lighting has been used to enhance the best possible way to acquire the image.  Enumeration of the dimensions is made through MATLAB software.  The dimensions of the boat structure were found to be 3.794 cm and of the indentation was found to be 1.8 mm.  This study underscores the importance of continued research and development in machine vision systems to fully realize their potential in industrial applications.